Are Eídōla Idols?: Probing a Lexicographical Trope - Chantziantoniou, Alexander (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
It has long been taken for granted that the use of εἴδωλον in the language of the Septuagint and its reception in early Jewish texts was unique within the history of postclassical Greek, imbued with pejorative meaning as a technical term of “Jewish Greek” that refers not to “images” but to “idols.” In this article, I interrogate the issues involved with this lexicographical commonplace and the translation practices it informs, and offer a critical reexamination of the literary and documentary evidence in which εἴδωλον occurs. I argue that the use of εἴδωλον in early Jewish Greek literature, from the Greek Pentateuch to Paul’s letters, was in fact remarkably unexceptional and readily recognisable as one lexical option among many in the diverse lexicon of cult images (e.g., ἄγαλμα, ἀνδριάς, ἀφίδρυμα, εἰκών, ἵδρυμα, ξόανον), just as it was in postclassical Greek more broadly. I conclude that transliterating εἴδωλον as “idol,” rather than translating it as “image,” keeps the illusion of uniqueness alive by inviting negative associations that closely align with its later lexicographical legacy but that do not clearly correspond to any known use of εἴδωλον in its own time and place.